TRIM71 Mutations Cause Human and Murine Congenital Hydrocephalus by Impairing Prenatal Neural Stem Cell Regulation. (16th November 2020) - Phan, Duy; Jin, Sheng C; Weise, Stefan; Marini, Claudia; Dong, Weilai; Kundishora, Adam; Torres-Fernandez, Lucia; Cuevas, Elisa; Hao, Le; Furey, Charuta G; Zeng, Xue; Jux, Bettina; et al.
Abstract: INTRODUCTION: Lack of understanding into the pathogenesis of congenital hydrocephalus (CH) hinders patient care and development of clinically-relevant animal models. Given that 40% of CH cases are thought to have a genetic etiology, human genetics is perhaps the most clinically relevant and unbiased approach to understanding biological mechanisms of CH. However, the overwhelming majority of patients remain genetically undefined, highlighting the urgent need for continued gene discovery. METHODS: We recruited 475 neurosurgically-treated primary CH probands, including 284 parent-offspring trios, and subjected them to whole exome sequencing (WES). Using CRISPR/Cas9 and mouse molecular genetic tools, we generated mutant mouse models harboring CH-causing mutations in genes identified by WES. RESULTS: We identify the let-7 microRNA target TRIM71/lin-41, encoding an RNA-binding protein enriched in mammalian embryonic neural stem cells (NSCs), to be the most commonly mutated gene in human CH. Three novel Trim71 mutant mouse models that harbor the homologous CH-causing point mutation localized to the TRIM71 RNA-binding domain or NSC-specific Trim71 deletion all exhibited severe neonatal-onset communicating hydrocephalus with cortical thinning observed in human patients. Strikingly, although the multiciliated ependyma and choroid plexus were normal in hydrocephalic Trim71 mutant mice, cortical neurogenesis was profoundly reduced due to premature neuronal differentiation at the expense of reduced NSC proliferative expansion in the embryonic neural tube. In vitro, CH-causing mutations impaired NSC proliferation and TRIM71's posttranscriptional regulation of RNA targets involved in stem cell proliferation and differentiation. CONCLUSION: Our data comprising of human genetics with functional validation in cell lines and three novel mutant mouse models (including the first-ever animal model in which a human-specific disease mutation has been shown to cause hydrocephalus) demonstrate TRIM71 is a bona fide CH gene and support a NSC paradigm of hydrocephalus.